Weltauflösungen Studien zu instabilen Erzählwelten in der deutschen und französischen Literatur (1945-1965) - Scherübl, Florian (Das Unsichere Wissen in der Literatur, 2023)
After WWII, a crisis of narrative worlds emerged in German and French literature. Narrative fiction, the main genre of world-making, created dissolving story worlds, which was a reaction to the critical and scientific attention being paid to the topic of 'Neuzeit' (modern history) after 1945. Even today, unstable narrative worlds present a challenge to the methods and instruments of narratological research and possible world theory. Located between the poetology of knowledge and possible world theory, this study analyses works by Gottfried Benn, Arno Schmidt, Wolfgang Hildesheimer, Peter Weiss, Samuel Beckett, Alain Robbe-Grillet and Maurice Blanchot. Their stories' dissolving worlds are used as a point of departure from which to tread new paths in world-based narratology.